PENGARUH KEUNGGULAN KOMPETITIF DAN BAURAN PEMASARAN TERHADAP KEBERHASILAN USAHATANI KOPI ARABIKA DI KABUPATEN SUKABUMI - Dewi Puspitasari Hasana; Euis Dasipah; Karyana KS; Nendah Siti Permana; Dety Sukmawati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Coffee is one of the most competitive plantation commodities. Where competitive advantage is one of the factors that affect the competitiveness of Indonesian coffee. In addition to competitiveness, another factor that affects the coffee commodity is the marketing mix. The government is trying to improve the competitiveness of local coffee in order to compete in the international market by increasing its advantages and expanding its marketing. This is what the Sukabumi district government has done. The purpose of this research is the effect of competitive advantage and marketing mix on the success of coffee farming. The method used is path analysis and farming analysis. The results of the analysis show that the F-count value is 153.112 where the value is greater than the F-table value, which is 3.183 at a significant level of 0.05, meaning that competitive advantage (X1) and marketing mix (X2) have a significantly positive effect on the success of coffee farming (Y). ). As for the value of R square, the value of R square is 0.869. This shows that the contribution or influence of X1 and X2 is 86.9 percent,